(untitled) (Western European Journal of Medicine and Medical Science, 2024)
In this study, the purity and amount of sodium (Na+ ) and potassium (K+ ) ions contained in the drug "Rehydrate Zinc" were determined using atomic absorption flame spectrometric methods (in the emission mode). The advantages of the combined use of atomic absorption and atomic emission spectrometric methods, the exclusion of destructive factors in the analysis of substances contained in complex drugs, the correct choice of a nebulizer and temperature, as well as the stability of the method when using highly sensitive methods were studied. The developed method of analytical analysis was validated for the following parameters: specificity, linearity, precision and reliability. The emission and atomic absorption flame spectrometric method can be used in manufacturing plants and research laboratories, in quality control and standardization of rehydrating solutions containing electrolytes, infusion solutions